AULACOGENS OF ANCIENT PLATFORMS: PROBLEMS OF THEIR ORIGIN AND TECTONIC DEVELOPMENT - Milanovsky E.E. (My University, 1981)
Riphean and Palaeozoic linear graben-like platform depressions — aulacogens —jointly with linear swell uplifts in a platform cover, intraplatform folded zones and Meso-Cenozoic epi-platform rift zones are different morphological manifestations of a single group of linear platform structures. Aulacogens are characterized by the long duration of their development and ability for regeneration. Their existence is certain, mainly since the Late Proterozoic (Riphean). Usually they inherit more ancient linear attenuated tectonic zones of platform basement or “adjust” to them. Aulacogens pass through common stages of development forming a single “cycle” or in many cases, even several similar though not identical “cycles”. The “cycle” starts with the incipience (or regeneration) of a linear graben-like depression limited by normal faults and after a more or less deep and long subsidence, accompanied often by basic or alkaline-basic volcanism, it is completed in many cases by an inversion stage. At this stage horst-like uplifts appear limited by thrust and overthrusts in the aulacogen basement, while linear swell-like uplifts or their systems and even linear folded structures occur in its cover. The early stages of an aulacogen evolution occur under horizontal extension conditions, whereas the inversion stage takes place under a compressional regime. “Cycles” of aulacogen development resemble (in attenuated, miniature form) the development “cycle” of adjacent geosynclinal areas, coincide with them in time and many “through” and “penetrating” aulacogens are their direct offsets.
Keywords: Cenozoic; Proterozoic; Palaeozoic; Riphean; Cenozoic; Кайнозой; Докембрий::Протерозой::Рифей; Precambrian::Proterozoic; Палеозой; Докембрий::Протерозой; Paleozoic; Precambrian::Proterozoic::Riphean